Konsumsi Makanan Ibu Hamil Berhubungan dengan Berat Badan Lahir Bayi di Daerah Pesisir - Juminten Saimin; Ade Rizky Amalia; Ashaeryanto Ashaeryanto; Asmarani Asmarani (Halu Oleo University, 2019)
ABSTRACTBackground: Low nutritional intake during pregnancy and nutritional status of pregnant women cause various effects for mother and babies. One of the effects is low birth weight. The prevalence of LBW in coastal areas is still high. This study aims to determine the relationship between eating habits of pregnant women with birth weight in coastal areas.Method: This study was an observational analytic study using a cross-sectional method. The sample were 50 respondents obtained using the consecutive sampling method. Data collection on eating habits used a food frequency questionnaire (FFQ). Data analysis used Fisher's Exact test with a significance value of p <0.05.Results: The results showed that infant birth weight in coastal areas was associated with the habits of pregnant women eating carbohydrate sources (p=0.45), protein sources (p=0.17) and vegetables (p=0.006). Infant birth weight in coastal areas was not related to the habits of pregnant women eating fruit (p=1.00). Conclusion: There was a relationship between infant birth weight in coastal areas and the habit of pregnant women eating carbohydrates sources, protein sources and vegetables. There was no relationship between infant birth weight in coastal areas and the habit of pregnant women eating fruits. Keywords :Birth weight, eating habits, pregnant women